PERSONALITY PROBLEMS - Khujamuradov Gofir Jurakulovich; Ubaydullaeva Shakhlo Berdibaevna; Hakimova Khanbuvi (American Journals Publishing, 2024)
Currently, one of the most important areas in the healthcare system is the study of quality of life in medicine. Such studies help to understand more deeply and thoroughly the problem of the patient’s attitude to his health. An important place in the study of the quality of life of patients belongs to the study of control over the medical care provided to the population. In this regard, the study of the quality of life and mental health of students is of particular interest.
Keywords: Quality of life, method, medicine.